Analytical determination of some mineral and trace elements in medicinal Castor plant (Ricinus communis L.) by instrumental neutron activation analysis - Bouzid Nedjimi (Journal of Trace Elements and Minerals, 2022)
Instrumental neutron activation analysis (INNA) has been applied to determine some mineral and trace elements (As, Ba, Br, Ca, Ce, Co, Cr, Cs, Eu, Fe, K, La, Na, Rb, Sb, Sc, Sm, Tb, Th, and Zn) in Ricinus communis L. (Euphorbiaceae family), a precious medicinal shrub used in Asian and north African countries, to treat multiple diseases and illnesses. The precision of method was evaluated by analyzing the certified reference material GBW 07605 (GSV-4) Tea leaves. The INNA analysis shows that Ca and K were the most abundant minerals in R. communis, followed by Na and Fe. The average estimation of daily intake of some chemical elements through the ingestion of 10 g of dry powder day−1person−1 contributes partially to the daily requirements of some essential elements such as Ca, Cr, Fe, and K. Furthermore arsenic (As) concentration in this shrub was below the allowable limit value recommended by world health organization. These data can be valuable for pharmaceutical and industrial purposes.